Reichsparteitag Nürnberg Ansichtskarte 1937 NSDAP Propaganda Richard... - Richard Borrmeister (Wikimedia Commons, 2019)
Carte postale ancienne issue de Wikimedia Commons. Titre: Reichsparteitag Nürnberg Ansichtskarte 1937 NSDAP Propaganda Richard BORRMEISTER Verlag Photo Hoffmann München Bund Deutscher Mädel BDM Jungmädelbund Reichsadler Nazi Rally Nuremberg Postcard No known copyright restrictions 8668. " Nuremberg Party Rally " (Reichsparteitag Nürnberg). Postcard showing a member of the Bund Deutscher Mädel (BDM) or Jungmädelbund | blonde girl with braids and flowers before a huge Nazi style Reichsadler (German imperial eagle) and Nuremberg castle | painting signed R. Borrmeister | published by Verlag Photo-Hoffmann, Munich | Nazi Party (NSDAP) propaganda
Droits : Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château; Carte postale